The Effect of E-Service Quality and E-Trust on Online Repurchase Intention Mediated by E-Satisfaction: A Study of Indonesian Auction Portal Consumers - Prayudi Utomo; Mochammad Farid Afandi; Novi Puspitasari (Harmony Management: International Journal of Management Science and Business, 2026)
This study examines the effect of e-service quality and e-trust on online repurchase intention, with e-satisfaction acting as a mediating variable among consumers of the Indonesian Auction Portal. The research employs a quantitative explanatory approach, with data collected from 101 respondents who have participated in at least two online auction transactions. The respondents were selected to ensure that they have sufficient experience in using the platform, thereby providing reliable insights into user behavior and perceptions. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS software to test both direct and indirect relationships among variables. The findings indicate that both e-service quality and e-trust have positive an significant effects on e-satisfaction as well as online repurchase intention. In addition, e-satisfaction is also found to have a positive and significant effect on online repurchase intention. More importantly, e-satisfaction fully mediates the relationship between e-service quality and online repurchase intention, as well as between e-trust and online repurchase intention, indicating that satisfaction plays a crucial role in translating service quality and trust into continued user engagement. These results highlight that user satisfaction is a central mechanism in strengthening customer loyalty and encouraging repeat usage behavior. Practically, the Indonesian State Assets and Auction Service Office (KPKNL) should focus on enhancing platform usability, service responsiveness, and trust-building mechanisms to improve user satisfaction and ensure sustainable participation in electronic auction services.